Interleukin-36γ Is Elevated in Cervicovaginal Epithelial Cells in Women With Bacterial Vaginosis and In Vitro After Infection With Microbes Associated With Bacterial Vaginosis - Gardner, Jameson K (J Infect Dis, 2020)
In recent studies, the interleukin (IL)-36 cytokines were shown to be elevated in women with non-Lactobacillus-dominated vaginal microbiomes. In this study, we evaluated IL36G expression in clinical samples from women with and without bacterial vaginosis (BV) and a human 3-dimensional cervical epithelial cell model. IL36G expression was significantly elevated in cervicovaginal epithelial cells isolated from BV-positive women and corresponded with increased neutrophil counts relative to BV-negative women. In addition, specific BV-associated bacterial species as well as a polymicrobial cocktail significantly induced IL36G expression in vitro. These findings suggest that IL-36γ may exhibit an important function in the host response to BV and other sexually transmitted infections.